Book Review: Language and Social Relations by Asif Agha, Cambridge University Press, New York, 2007, 427 pages - Sukardi Weda (Institut Agama Islam Negeri Palopo, 2015)
Book Review Language and Social Relations by Asif Agha, Cambridge University Press, New York, 2007, 427 pagesAnalyzed by: Sukardi Weda, English Language and Literature Department, Faculty of Languages and Literatures, State University of Makassar, Makassar, Indonesia, sukardiweda@yahoo.com